Perempuan Desa Dan Pendidikan Ekonomi: Antara Pengetahuan Dan Praktik Dalam Usaha Keluarga - Indrayani, Luh; Santi, Ni Wayan Ayu; Meitriana, Made Ary (Jambura Economic Education Journal, 2026)
This study aims to bridge the gap between the economic knowledge and practices of rural women, and to formulate a locally-based economic education approach that can empower women in a contextual and sustainable manner. This study uses a qualitative (grounded) approach with interviews, observations, and focus group discussions (FGD) to explore the economic knowledge of rural women regarding family economic practices. This study uses data collection techniques in the form of observations and interviews. The results of this study are (1) the level of economic knowledge possessed by women in Sembiran Village does not come from formal education, but rather from life experiences, social interactions, and local traditions, (2) the economic practices carried out by women in family businesses in Sembiran Village utilize social networks for marketing, demonstrating economic intelligence that is not always recorded in education statistics, and (3) There is a close relationship between economic knowledge and economic practices carried out by women; both formal and informal economic education can increase the capacity of rural women in managing family businesses.